Mongolia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2021)
A strong export-led recovery is underway. Despite early actions and a successful vaccination campaign, the pandemic is lingering in Mongolia as positivity rates remain high and borders largely closed. An export-led recovery which began in mid-2020, is gathering steam due to booming prices for Mongolia's exports. Nevertheless, domestic demand, labor markets and the business sector remain weak. Policies were appropriately supportive during the pandemic. However, large, untargeted and continuing fiscal, quasi-fiscal and financial forbearance measures legislated by Parliament have heightened macrofinancial vulnerabilities: public debt has sharply increased, bank balance sheets have further weakened, and the Bank of Mongolia's (BOM) operational independence has been compromised. On the plus side, external and fiscal buffers have been built, helped by the 2021 IMF SDR allocation of USD 98.3 million (95.8 percent of quota), and the rollover of large external liabilities has increased policy space.